Ginger on Human Health: A Comprehensive Systematic Review of 109 Randomized Controlled Trials - Anh, Nguyen Hoang; Kim, Sun Jo; Long, Nguyen Phuoc; Min, Jung Eun; Yoon, Young Cheol; Lee, Eun Goo; Kim, Mina; Kim, Tae Joon; Yang, Yoon Young; Son, Eui Young; Yoon, Sang Jun; Diem, Nguyen Co; et al. (Nutrients, 2020)
Clinical applications of ginger with an expectation of clinical benefits are receiving significant attention. This systematic review aims to provide a comprehensive discussion in terms of the clinical effects of ginger in all reported areas. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guideline, randomized controlled trials on the effects of ginger were investigated. Accordingly, 109 eligible papers were fully extracted in terms of study design, population characteristics, evaluation systems, adverse effects, and main outcomes. The reporting quality of the included studies was assessed based on the Cochrane Collaboration’s tool for assessing the risk of bias in randomized trials and integrated together with studies that investigated the same subjects. The included studies that examined the improvement of nausea and vomiting in pregnancy, inflammation, metabolic syndromes, digestive function, and colorectal cancer’s markers were consistently supported, whereas other expected functions were relatively controversial. Nevertheless, only 43 clinical trials (39.4%) met the criterion of having a ‘high quality of evidence.’ In addition to the quality assessment result, small populations and unstandardized evaluation systems were the observed shortcomings in ginger clinical trials. Further studies with adequate designs are warranted to validate the reported clinical functions of ginger.